Low back pain in elite track and field athletes. Issue 2 (20th January 2011) - Malliaropoulos, N; Bikos, G; Tsitas, K; Papadopoulou, S
Abstract : Introduction: Low back pain is an extremely common symptom, not a disease, and has many causes with disc pathology being the underlying reason in most of the cases.The aim of this study was to investigate and compare the causes of low back pain (LBP) in elite track and field athletes of their different events. Material and method: Retrospective cohort study of S.E.G.A.S. sports clinic LBP reports compiled by certified physicians between 1988 and 2008.The participants were 18–26 year-old male and female elite track and field athletes with low bak pain. The main outcome measure was an analysis of aetiology of LBP at three event category athletes: throwers, jumpers, and sprinters and their lumbar pain problems were categorised at discogenic (disk herniation, derangement, bulging), muscle injuries, back element injuries (spondylolysis, spondylolisthesis, facet joint syndrome), complex injuries (combination of the categories above) and other problems (Scheuerman disease, compresion fractures, etc). Results: Ninety four athletes with low back pain (44 sprinters, 29 throwers and 44 jumpers) which visited the sport clinic totaly 184 times (a percentage of 3.6% at a total number of 2591 injured athletes) were included in the study. When evaluating all events concurrently discogenic problems were the most common cause of low back pain followed in descending order by muscle and back elements injuries with the same percentage and complex problems with the discogenic causal element prevailed. Conclusion: When evaluating all these three categories emerges clearly the prevalence of discogenic aetiology lumbar pain in these categories of athletes.